Appropriate Accommodation For Students With Disabilities (Case Study: UPN “Veteran” East Java) - Cinta Pratama Putri Suwanto; Sri Wibawani (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The current state of universities shows a gap between policies and the implementation of adequate accommodation, necessitating a study of university strategies in realizing inclusive services. Likewise, UPN “Veteran” East Java has also developed an appropriate strategy and provided solutions to accommodation-related problems, especially for students with disabilities. This study aims to analyze UPN “Veteran” East Java's strategy in providing adequate accommodation for students with disabilities, including strategy formulation, implementation, and evaluation. This study used a qualitative approach with data collection techniques through interviews, observation, and documentation. The results showed that at the formulation stage, the university had a strong strategic foundation through institutional values, SWOT analysis, and participatory formulation of its vision and mission. At the implementation stage, an inclusiveness policy was in place, but there were still obstacles to inclusive learning, an unintegrated information system, and suboptimal data collection and coordination. At the evaluation stage, the system was running at the program, individual, and institutional levels, but user feedback was not optimal. Overall, the inclusiveness strategy was running but still needed strengthening in the aspects of implementation and participatory evaluation.